Development of Thai Verse Composition Skills through Instructional Songs Integrated with a Coaching Process among Grade 7 Students in Class 1/6 at Mahannaparam School - Sriphrachan, Natthakorn; Praisorn, Benjaporn (ARU Research Journal Humanities and Social Sciences, 2026)
This classroom action research aimed to the effects of using instructional songs integrated with a coaching process on the development of Thai verse composition skills among Grade 7 students in Class 1/6 at Mahannaparam School during the 2025 academic year; (2) compare the students’ understanding of prosodic conventions and verse structure before and after the intervention; and (3) examine changes in their attitudes and motivation toward learning Thai verse composition. The target group consisted of five Grade 7 students in class 1/6, through purposive sampling during the 2025 academic year. These participants initially demonstrated insufficient mastery of prosodic rules and failed to meet standardized learning indicators. The research was conducted in three phases: (1) investigating and analyzing the instructional problems; (2) developing an instructional approach that integrated instructional songs with a coaching process; and (3) implementing the instructional innovation to develop the students’ verse composition skills. The research instruments consisted of four lesson plans and an instructional Ramwong song on Kap Yani 11 verse. The findings indicated that the Thai verse composition skills of all five students improved, and each student achieved the predetermined criterion of 60%. Their understanding of prosodic conventions and verse structure after the intervention was higher than before the intervention. The students also demonstrated more positive attitudes and greater motivation toward learning Thai verse composition, as reflected in their increased confidence and active participation. The findings suggest that the integration of instructional songs and a coaching process can support the development of Thai verse composition skills, understanding of poetic conventions, and learning motivation among the target students.